Reading Esther intertextually - Firth, David G.; Melton, Brittany N. (Library of Hebrew bible/Old Testament studies, 2022)
Cover -- Series -- Title -- Copyright -- Dedication -- Contents -- Tables -- Contributors -- Preface -- Abbreviations -- Under the Intertextual Umbrella: An Introduction -- Part I Esther in Dialogue with the Torah -- Chapter 1 Foreign Ambivalence in the Scroll: Reading Esther's Court alongside Joseph and Daniel (Gabriel F. Hornung) -- Chapter 2 The Book of Esther: Exodus, Passover, and Food-Laws (J. Gordon McConville) -- Part II Esther in Dialogue with the Former Prophets -- Chapter 3 Esther and Joshua: Negotiating Identity in and out of the Land (David G. Firth) -- Chapter 4 Eyes, Hearts, and Doing "what seems good": Reading Judges and Esther Side-by-Side (Isabelle Hamley) -- Chapter 5 Overturning Sovereignty: Esther in Dialogue with the Book of Samuel (Rachelle Gilmour) -- Part III Esther in Dialogue with the Latter Prophets -- Chapter 6 At the Table: Banquets in Esther and Isaiah in Intertextual Conversation (Andrew T. Abernethy) -- Chapter 7 The Fruit of Mourning: Esther Enriched by the Latter Prophets (Heath A. Thomas) -- Part IV Esther in Dialogue with the Writings -- Chapter 8 In a World without God: Reading Esther Alongside Psalms (David G. Firth and Brittany N. Melton) -- Chapter 9 Reading Esther with Proverbs: Complexifying Character, Theme, and Ideology (Suzanna R. Millar) -- Part V Esther in Dialogue beyond the Hebrew Bible -- Chapter 10 Trauma, Purity, and Danger in the LXX Prayers of Esther and Judith (Helen Efthimiadis-Keith (Keith-van Wyk)1 -- Chapter 11 Esther in Dialogue with the Qumran Community (Seulgi L. Byun) -- Chapter 12 Reading Josephus Reading Esther (Paul Spilsbury) -- Chapter 13 Esther in Dialogue with Mark: Power, Vulnerability, and Kingship (Kara J. Lyons-Pardue) -- Chapter 14 Reading Esther in Dialogue with the Rabbis (Jonathan Grossman).